A temperature-adjustable thermal conductive phase change composite material and its preparation method and application

By combining inorganic phase change materials, nucleating agents, thickening agents, thermal conductivity fillers and temperature regulators, a thermally adjustable thermal phase change composite material is prepared, which solves the problems of narrow phase change temperature range, limited thermal conductivity and large supercooling degree of existing materials, and achieves efficient utilization of latent phase change heat and excellent thermal conductivity.

CN118027905BActive Publication Date: 2025-03-28SICHUAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410166680.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-06
Publication Date
2025-03-28
Estimated Expiration
2044-02-06

AI Technical Summary

Technical Problem

The existing phase change composite materials have narrow phase change temperature range, limited thermal conductivity and large supercooling degree, resulting in low latent heat utilization rate of phase change.

Method used

By combining inorganic phase change materials, nucleating agents, thickening agents, thermal fillers and temperature regulators, a temperature-adjusted thermal phase change composite material is prepared. The material improves thermal conductivity by introducing thermal fillers, introduces a temperature regulator to adjust the phase change temperature, and forms a support network structure through thickeners to inhibit phase separation and improve stability.

Benefits of technology

The adjustability of the phase change temperature is achieved, the latent heat and thermal conductivity of the phase change are improved, and the supercooling degree is reduced, thereby improving the efficiency and stability of the energy storage and energy release of the phase change material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118027905B_ABST
    Figure CN118027905B_ABST
Patent Text Reader

Abstract

The present application discloses a temperature-adjustable thermally conductive phase-change composite material and its preparation method and application, which belongs to the technical field of phase-change heat storage materials. The temperature-adjustable thermally conductive phase-change composite material provided by the present application is compounded by a certain proportion of inorganic phase-change material, nucleating agent, thickener, thermally conductive filler and temperature regulator, and its phase change temperature is 26.2-34.2°C, supercooling is 0.1°C, phase change latent heat is 103.7-170.2J / g, and thermal conductivity is 1.12-1.55W / m·K. The preparation method provided by the present application melt-blends inorganic phase-change material, nucleating agent, thickener, thermally conductive filler and temperature regulator, stirs evenly, and then cools to obtain a temperature-adjustable thermally conductive phase-change composite material, so that the temperature-adjustable thermally conductive phase-change composite material has a phase change temperature close to room temperature and a high phase change latent heat value, excellent thermal conductivity and low supercooling, and has a wide range of applications in battery outer packaging thermal management, wearable thermal management equipment and energy-saving building materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of phase change heat storage materials, and in particular, relates to a temperature-adjustable thermally conductive phase change composite material and a preparation method and application thereof. Background Art

[0002] Phase change heat storage materials can be divided into inorganic phase change materials and organic phase change materials. Among them, inorganic phase change materials have more practical value in thermal management applications due to their high energy storage density, suitable phase change temperature, low price, and the advantage of being non-flammable compared to organic phase change materials. However, due to the crystal structure of inorganic phase change materials, their phase change latent heat at room temperature is generally low and their thermal conductivity is limited, which greatly limits their application. Therefore, it is necessary to improve the phase change latent heat and thermal conductivity of inorganic phase change materials at room temperature.

[0003] The prior art with the announcement number CN 1100849310 B discloses a composite phase change material, which uses a sol-gel method to make disodium hydrogen phosphate dodecahydrate, capric acid and a thickener into a gel, and then performs a cooling and heating cycle to prepare a composite phase change material with high latent heat of phase change.

[0004] However, the composite phase change material described above has the following problems: first, the adjustable range of the phase change temperature of the composite phase change material is narrow, and its phase change latent heat is low within the phase change temperature range; second, the thermal conductivity is low, resulting in its inability to store and release energy in time; third, the supercooling is large, resulting in the dissipation of the phase change latent heat of the phase change material, resulting in low utilization rate of the phase change latent heat. Summary of the invention

[0005] The present application discloses a temperature-adjustable thermally conductive phase-change composite material and a preparation method and application thereof, aiming to solve the technical problems of the existing phase-change composite materials such as narrow phase-change temperature range, limited thermal conductivity and large supercooling.

[0006] In order to achieve the above purpose, the technical solution of this application is:

[0007] The first aspect of the present application provides a temperature-adjustable thermally conductive phase-change composite material, the raw materials for preparing the composite material are composed of the following components:

[0008] 50-90 parts by weight of inorganic phase change material;

[0009] Nucleating agent 0-5 parts by weight;

[0010] Thickener 0-5 parts by weight;

[0011] Thermally conductive filler 0-5 parts by weight;

[0012] Temperature regulator 0-10 parts by weight.

[0013] In combination with the first aspect, preferably, the inorganic phase change material includes one or more of sodium sulfate, disodium hydrogen phosphate, sodium acetate, calcium chloride and sodium carbonate hydrate salts.

[0014] In combination with the first aspect, preferably, the nucleating agent includes one or more of borax, silicon dioxide, aluminum oxide, chitin nanowhiskers, graphene oxide, nanocopper, and magnesium chloride hexahydrate.

[0015] In combination with the first aspect, preferably, the thickener includes one or more of sodium polyacrylate, polyacrylamide, bacterial cellulose, hydroxymethyl cellulose, and polyanionic cellulose.

[0016] In combination with the first aspect, preferably, the thermally conductive filler includes one or more of expanded graphite, boron nitride, aluminum nitride, graphene, aluminum dioxide, graphite oxide, carbon nanotubes, titanium dioxide, nanosilver, nanocopper, and nanoiron oxide.

[0017] In combination with the first aspect, preferably, the temperature regulator includes one or more of potassium chloride, ammonium chloride and sodium chloride.

[0018] The second aspect of the present application provides a method for preparing the temperature-adjustable thermally conductive phase change composite material according to the first aspect, the method comprising:

[0019] The inorganic phase change material, the nucleating agent and the thickener are blended and melted, and then cooled to obtain a first composite;

[0020] The first composite and the thermally conductive filler are blended and melted, and then cooled to obtain a second composite;

[0021] The second composite and the temperature regulator are blended and melted, and then cooled to obtain the temperature-adjustable thermally conductive phase-change composite material.

[0022] In combination with the second aspect, preferably, during the blending and melting, the temperature is 40-80° C. and the time is 0.2-2 h.

[0023] In combination with the second aspect, preferably, the cooling temperature is -196-10°C.

[0024] The third aspect of the present application provides the application of the temperature-adjustable thermally conductive phase-change composite material prepared by the preparation method of the second aspect in battery thermal management, wearable thermal management devices and energy-saving building materials.

[0025] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present application include at least:

[0026] The temperature-adjustable thermally conductive phase-change composite material provided in the present application is obtained by compounding an inorganic phase-change material, a nucleating agent, a thickener, a thermally conductive filler and a temperature regulator. On the one hand, the introduction of the thermally conductive filler not only improves the thermal conductivity of the material, but also can cooperate with the thickener to inhibit phase separation, improve the cyclic stability of the composite material, and provide heterogeneous nucleation sites, reduce the crystallization energy barrier and promote crystallization, thereby maintaining a high phase change latent heat of the phase change material; on the second hand, the introduction of the temperature regulator can make the hydrolyzed cations distributed between the water molecules and the inorganic phase change material molecules, increase the binding resistance between the inorganic phase change material molecules and the water molecules, and thus reduce the phase change temperature; on the third hand, the introduction of a thickener with a large specific surface area and abundant hydroxyl groups can form a supporting network structure, which can not only form hydrogen bond interactions with water molecules, significantly improve the stability of the phase change material and effectively inhibit phase separation, but also facilitate the thermally conductive filler to construct a heat conduction path and strengthen the heat transfer path. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0028] Figure 1 The step cooling curves of the temperature-adjustable thermally conductive phase change composite materials 5BN-KN1, 5BN-KN3, 5BN-KN5 and 5BN-KN7 prepared in the examples of the present application;

[0029] Figure 2 Phase separation diagram of the temperature-adjustable thermally conductive phase change composite materials 5BN-KN1, 5BN-KN3, 5BN-KN5 and 5BN-KN7 prepared in the examples of the present application;

[0030] Figure 3 Phase change latent heat and phase change temperature diagram of the temperature-adjustable thermal conductive phase change composite materials 5BN-KN1, 5BN-KN3, 5BN-KN5 and 5BN-KN7 prepared in the examples of the present application;

[0031] Figure 4 The latent heat of phase change and the phase change temperature diagram of the temperature-adjustable thermal conductive phase change composite materials of 1BN-KN3, 3BN-KN3 and 5BN-KN3 prepared in the examples of the present application;

[0032] Figure 5 This is a cyclic stability diagram of the 5BN-KN3 temperature-adjustable thermally conductive phase change composite material prepared in an embodiment of the present application;

[0033] Figure 6This is a thermal conductivity diagram of the temperature-adjustable thermally conductive phase change composite materials 1BN-KN3, 3BN-KN3 and 5BN-KN3 prepared in the examples of the present application. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0035] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0036] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0037] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0038] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0039] It should be noted that all raw materials and reagents in the examples of the present application are purchased on the market or prepared according to conventional methods well known to those skilled in the art. For example, sodium sulfate hydrate, disodium hydrogen phosphate hydrate, sodium acetate hydrate, calcium chloride hydrate, sodium carbonate hydrate, borax, silicon dioxide, aluminum oxide, chitin nano whiskers, graphene oxide, nano silver, nano copper, magnesium chloride hexahydrate, carbon nanotubes, sodium polyacrylate, polyacrylamide, bacterial cellulose, hydroxymethyl cellulose, polyanionic cellulose, etc. are all purchased on the market.

[0040] In a first aspect, an embodiment of the present application provides a temperature-adjustable thermally conductive phase change composite material, the raw materials for preparing which are composed of the following components: 50 to 90 parts by weight of inorganic phase change material; 0 to 5 parts by weight of nucleating agent; 0 to 5 parts by weight of thickener; 0 to 5 parts by weight of thermally conductive filler; and 0 to 10 parts by weight of temperature regulator.

[0041] Among them, on the one hand, the introduction of thermally conductive fillers can not only improve the thermal conductivity of the material, but also cooperate with the thickener to inhibit phase separation, improve the cyclic stability of the composite material, and provide heterogeneous nucleation sites, reduce the crystallization energy barrier and promote crystallization, thereby maintaining the high phase change latent heat of the phase change material; on the second hand, the introduction of temperature regulators can make the hydrolyzed cations distributed between water molecules and inorganic phase change material molecules, increase the binding resistance between inorganic phase change material molecules and water molecules, and thus reduce the phase change temperature; on the third hand, the introduction of thickeners with large specific surface area and rich hydroxyl groups can form a supporting network structure, which can not only form hydrogen bond interactions with water molecules, significantly improve the stability of the phase change material and effectively inhibit phase separation, but also help the thermally conductive fillers to build heat conduction pathways and strengthen heat transfer paths.

[0042] In the embodiment of the present application, the inorganic phase change material is preferably one or more of sodium sulfate (Na2SO4), disodium hydrogen phosphate (Na2HPO4), sodium acetate (CH3COONa), calcium chloride (CaCl2) and sodium carbonate (Na2CO3) hydrated salts. Among them, these materials have the characteristics of high energy density and strong energy storage capacity, which can effectively ensure the energy storage density of the thermal conductive phase change composite material.

[0043] In the embodiment of the present application, the nucleating agent is preferably one or more of borax, silicon dioxide, aluminum oxide, chitin nano whiskers, graphene oxide, nano copper, and magnesium chloride hexahydrate. Among them, these nucleating agents have similar lattice parameters to the inorganic phase change material, can play a role in inducing crystallization, and achieve the purpose of reducing supercooling.

[0044] In the embodiment of the present application, the thickener is preferably one or more of sodium polyacrylate, polyacrylamide, bacterial cellulose (BC), hydroxymethyl cellulose, and polyanionic cellulose. Among them, the surface of these thickeners has a high specific surface area and abundant hydroxyl or amide groups, which can form a network structure, not only can form hydrogen bond interactions with water molecules, significantly improve the stability of phase change materials and effectively inhibit phase separation, but also help thermal conductive fillers to build heat conduction paths and strengthen heat transfer paths.

[0045] In the embodiment of the present application, the thermally conductive filler is preferably one or more of expanded graphite, boron nitride (BN), aluminum nitride, graphene, aluminum dioxide, graphite oxide, carbon nanotubes, titanium dioxide, nanosilver, nanocopper, and nanoiron oxide. In addition, the addition of these thermally conductive fillers can not only improve the thermal conductivity of the material, but also cooperate with the thickener to inhibit phase separation, improve the cyclic stability of the composite material, and provide heterogeneous nucleation sites, reduce the crystallization energy barrier and promote crystallization, thereby maintaining a high phase change latent heat of the phase change material.

[0046] In the embodiment of the present application, the temperature regulator is preferably one or more of potassium chloride (KCl), ammonium chloride (NH4Cl) and sodium chloride (NaCl). The addition of these temperature regulators allows the hydrolyzed cations to be distributed between water molecules and inorganic phase change material molecules, increasing the binding resistance between inorganic phase change material molecules and water molecules, thereby reducing the phase change temperature.

[0047] In a second aspect, the present invention provides a method for preparing the temperature-adjustable thermally conductive phase change composite material described in the present invention, the preparation method comprising:

[0048] The inorganic phase change material, the nucleating agent and the thickener are blended and melted, and then cooled to obtain a first composite;

[0049] The first composite and the thermally conductive filler are blended and melted, and then cooled to obtain a second composite;

[0050] The second composite and the temperature regulator are blended and melted, and then cooled to obtain the temperature-adjustable thermally conductive phase-change composite material.

[0051] In the embodiment of the present application, the temperature during the blending and melting is 40-80°C and the time is 0.2-2h. For example, the temperature is preferably 40°C, 50°C, 60°C, 70°C, 80°C or any temperature within the range; the time is preferably 0.2-2h, for example, 0.2h, 0.5h, 1h, 1.5h, 2h or any time within the range. Among them, by controlling the reaction temperature and reaction time, the crystal nucleation and growth process can be promoted to form a uniform and stable mixture.

[0052] In the embodiment of the present application, the cooling temperature is -196-10°C, for example, the temperature is preferably -196°C, -170°C, -150°C, -100°C, -50°C, 0°C, 10°C or any temperature within the range. By controlling the cooling temperature, the efficient nucleation process can be ensured and the production cycle can be controlled.

[0053] On the third aspect, the embodiments of the present application also provide the application of the temperature-adjustable thermally conductive phase change composite material in thermal management of battery outer packaging, wearable thermal management equipment and energy-saving building materials. Among them, the temperature-adjustable thermally conductive phase change composite material is used as a packaging medium for thermal management of battery outer packaging; as a functional component, it is integrated with fabrics or films to develop wearable thermal management equipment; it is loaded on the building maintenance fence structure (floor, wall, concrete, etc.) to achieve energy-saving building temperature control. Based on the above-mentioned temperature-adjustable thermally conductive phase change composite material, it has the advantages of low supercooling, phase change temperature close to room temperature, high latent heat and excellent thermal conductivity. Therefore, when the temperature-adjustable thermally conductive phase change composite material of the embodiment of the present application is used in thermal management of battery outer packaging, wearable thermal management equipment and energy-saving buildings, it has the advantages of low supercooling, phase change temperature close to room temperature, high latent heat and excellent thermal conductivity.

[0054] The technical solution of the present application will be further described below in conjunction with specific embodiments.

[0055] Example 1

[0056] This embodiment provides a method for preparing a 5BN-KN1 temperature-adjustable thermally conductive phase change composite material, which specifically includes:

[0057] S101: 2.14 g Na2SO4 and 0.15 g borax were added to 2.71 g BC (solid content 0.8 wt%) aqueous dispersion, stirred thoroughly, heated in a 60°C water bath with stirring for 30 min, and then cooled at 0°C to obtain sample A1;

[0058] S102: 0.25 g of BN was added to 4.75 g of sample A1, heated in a water bath at 60° C. with stirring for 30 min, and cooled at 0° C. to obtain a thermally conductive phase change material, named 5BN;

[0059] S103: Add 0.05 g of KCl-NH4Cl mixed salt to 4.95 g of sample 5BN in a ratio of KCl:NH4Cl of 1:4, heat and stir in a 60°C water bath for 30 min, and cool to 0°C to obtain a temperature-adjustable thermal conductive phase change composite material of sample 5BN-KN1.

[0060] Example 2

[0061] This embodiment provides a method for preparing a 5BN-KN3 temperature-adjustable thermally conductive phase change composite material, which specifically includes:

[0062] S201: 2.14 g Na2SO4 and 0.15 g borax were added to 2.71 g BC (solid content 0.8 wt%) aqueous dispersion, stirred thoroughly, heated in a 60°C water bath with stirring for 30 min, and then cooled at 0°C to obtain sample A1;

[0063] S202: Then, 0.25 g of BN was added to 4.75 g of sample A1, heated in a water bath at 60° C. with stirring for 30 min, and cooled at 0° C. to obtain a thermally conductive phase change material, named 5BN;

[0064] S203: Add 0.15 g of KCl-NH4Cl mixed salt to 4.85 g of sample 5BN in a ratio of KCl:NH4Cl of 1:4, heat and stir in a 60°C water bath for 30 min, and cool to 0°C to obtain sample 5BN-KN3 temperature-adjustable thermal conductive phase change composite material.

[0065] Example 3

[0066] This embodiment provides a method for preparing a 5BN-KN5 temperature-adjustable thermally conductive phase change composite material, which specifically includes:

[0067] S301: 2.14 g Na2SO4 and 0.15 g borax were added to 2.71 g BC (solid content 0.8 wt%) aqueous dispersion, stirred thoroughly, heated in a 60°C water bath with stirring for 30 min, and then cooled at 0°C to obtain sample A1;

[0068] S302: 0.25 g of BN was added to 4.75 g of sample A1, heated in a water bath at 60° C. with stirring for 30 min, and cooled at 0° C. to obtain a thermally conductive phase change material, named 5BN;

[0069] S303: Add 0.25 g of KCl-NH4Cl mixed salt to 4.75 g of sample 5BN in a ratio of KCl:NH4Cl of 1:4, heat in a 60°C water bath with stirring for 30 min, and cool at 0°C to obtain a temperature-adjustable thermal conductive phase change composite material of sample 5BN-KN5.

[0070] Example 4

[0071] This embodiment provides a method for preparing a 5BN-KN7 temperature-adjustable thermally conductive phase change composite material, which specifically includes:

[0072] S401: 2.14 g Na2SO4 and 0.15 g borax were added to 2.71 g BC (solid content 0.8 wt%) aqueous dispersion, stirred thoroughly, heated in a 60°C water bath with stirring for 30 min, and then cooled at 0°C to obtain sample A1;

[0073] S402: 0.25 g of BN was added to 4.75 g of sample A1, heated in a water bath at 60° C. with stirring for 30 min, and cooled at 0° C. to obtain a thermally conductive phase change material, named 5BN;

[0074] S403: Add 0.35 g of KCl-NH4Cl mixed salt to 4.65 g of sample 5BN in a ratio of KCl:NH4Cl of 1:4, heat in a 60°C water bath with stirring for 30 min, and cool at 0°C to obtain sample 5BN-KN7, a temperature-adjustable thermal conductive phase change composite material.

[0075] Example 5

[0076] This embodiment provides a method for preparing a 3BN-KN3 temperature-adjustable thermally conductive phase change composite material, which specifically includes:

[0077] S501: 2.14 g Na2SO4 and 0.15 g borax were added to 2.71 g BC (solid content 0.8 wt%) aqueous dispersion, stirred thoroughly, heated in a 60°C water bath with stirring for 30 min, and then cooled at 0°C to obtain sample A1;

[0078] S502: 0.15 g of BN was added to 4.85 g of sample A1, heated in a water bath at 60° C. with stirring for 30 min, and cooled at 0° C. to obtain a thermally conductive phase change material, named 3BN;

[0079] S503: Add 0.15 g of KCl-NH4Cl mixed salt to 4.85 g of sample 3BN in a ratio of KCl:NH4Cl of 1:4, heat in a 60°C water bath with stirring for 30 min, and cool at 0°C to obtain a temperature-adjustable thermal conductive phase change composite material of sample 3BN-KN3.

[0080] Example 6

[0081] This embodiment provides a method for preparing a 1BN-KN3 temperature-adjustable thermally conductive phase change composite material, which specifically includes:

[0082] S601: Add 2.14 g Na2SO4 and 0.15 g borax to 2.71 g BC (solid content 0.8 wt%) aqueous dispersion, stir well, heat and stir in a 60°C water bath for 30 min, and then cool at 0°C to obtain sample A1;

[0083] S602: 0.05 g of BN was added to 4.95 g of sample A1, heated in a water bath at 60° C. with stirring for 30 min, and cooled at 0° C. to obtain a thermally conductive phase change material, named 1BN;

[0084] S603: Add 0.15 g of KCl-NH4Cl mixed salt to 4.85 g of sample 1BN in a ratio of KCl:NH4Cl of 1:4, heat in a 60°C water bath with stirring for 30 min, and cool to 0°C to obtain sample 1BN-KN3 temperature-adjustable thermal conductive phase change composite material.

[0085] Example 7

[0086] This embodiment provides a method for preparing a temperature-adjustable thermally conductive phase change composite material, which specifically includes:

[0087] S701: 1.92 g Na2HPO4 and 0.15 g silicon dioxide were added to 2.93 g sodium polyacrylate aqueous dispersion, wherein the mass fraction of sodium polyacrylate was 0.8 wt %, and the mixture was stirred evenly. The mixture was heated in a water bath at 40° C. with stirring for 30 min, and then cooled at 10° C. to obtain sample A2.

[0088] S702: 0.25 g of expanded graphite (EG) was added to 4.75 g of sample A2, heated in a water bath at 40°C with stirring for 30 min, and cooled at 10°C to obtain a thermally conductive phase change material, named ɑ-1EG;

[0089] S703: Add 0.15 g of NaCl-NH4Cl mixed salt to 4.85 g of sample ɑ-1EG in a ratio of NaCl:NH4Cl of 1:4, heat and stir in a water bath at 40°C for 30 min, and cool at 10°C to obtain sample ɑ7, a temperature-adjustable thermal conductive phase change composite material.

[0090] Example 8

[0091] This embodiment provides a method for preparing a temperature-adjustable thermally conductive phase change composite material, which specifically includes:

[0092] S801: Add 2.46 g of CaCl2 and 0.15 g of magnesium chloride hexahydrate to 2.39 g of polyacrylamide aqueous dispersion, wherein the mass fraction of polyacrylamide is 0.8 wt %, stir well, heat and stir in a water bath at 80° C. for 30 min, and then cool at 10° C. to obtain sample A3;

[0093] S802: 0.25 g of expanded graphite (EG) was added to 4.75 g of sample A3, heated in a water bath at 80°C with stirring for 30 min, and cooled at 10°C to obtain a thermally conductive phase change material, named ɑ-2EG;

[0094] S803: Add 0.15 g of NaCl-NH4Cl mixed salt to 4.85 g of sample ɑ-2EG in a ratio of NaCl:NH4Cl of 1:4, heat and stir in a water bath at 80°C for 30 min, and cool at -196°C to obtain sample ɑ8, a temperature-adjustable thermal conductive phase change composite material.

[0095] At the same time, in order to verify the physical and chemical properties of the temperature-adjustable thermally conductive phase-change composite material prepared in the above embodiment, the present application provides the following comparative examples for detailed description.

[0096] Comparative Example 1

[0097] This comparative example provides a method for preparing a β1 phase change composite material, which specifically includes:

[0098] S901: Add 2.14g Na2SO4 and 0.15g borax to 2.71g BC (solid content 0.8wt%) aqueous dispersion, stir well, heat and stir in a 60℃ water bath for 30min, and then cool at 0℃ to obtain sample β1 phase change composite material.

[0099] The phase change temperature of the phase change composite material measured by differential scanning calorimetry (DSC) is 35.7°C, and the phase change enthalpy is 231.9 J / g; the thermal conductivity of the phase change material measured by hot disk is 0.6 W / m·K.

[0100] Comparative Example 2

[0101] This comparative example provides a method for preparing a β2 phase change composite material, which specifically includes:

[0102] S1001: Add 2.14g Na2SO4 and 0.15g borax to 2.71g BC (solid content 0.8wt%) aqueous dispersion, stir well, heat in a 60℃ water bath with stirring for 30min, and then cool at 0℃ to obtain sample A1; then take 0.25g BN and add it to 4.75g sample A1, heat in a 60℃ water bath with stirring for 30min, and cool at 0℃ to obtain β2 thermal conductive phase change composite material.

[0103] The phase change temperature of the phase change composite material measured by differential scanning calorimetry (DSC) is 37.1°C, and the phase change enthalpy is 208.1 J / g; the thermal conductivity of the phase change material measured by hot disk is 1.34 W / m·K.

[0104] Comparative Example 3

[0105] This comparative example provides a method for preparing a β3 phase change composite material, specifically comprising: KN1

[0106] S1101: Add 2.14 g Na2SO4 and 0.15 g borax to 2.71 g (solid content 0.8 wt%) aqueous BC dispersion, stir well, heat and stir in a 60°C water bath for 30 min, and then cool at 0°C to obtain sample A1.

[0107] S1102: Add 0.05 g of KCl-NH4Cl mixed salt to 4.95 g of sample A1 in a ratio of KCl:NH4Cl of 1:4, heat in a water bath at 60°C with stirring for 30 min, and cool at 0°C to obtain a sample β3 phase change composite material.

[0108] The phase change temperature of the phase change composite material measured by differential scanning calorimeter (DSC) is 35.3°C, and the phase change enthalpy is 204.6J / g; the thermal conductivity of the phase change material measured by hot disk is 0.73W / m·K.

[0109] Comparative Example 4

[0110] This comparative example provides a method for preparing a β4 phase change composite material, which specifically includes:

[0111] S1201: Add 2.14 g Na2SO4 and 0.15 g borax to 2.71 g BC (solid content 0.8 wt%) aqueous dispersion, stir well, heat and stir in a 60°C water bath for 30 min, and then cool at 0°C to obtain sample A1.

[0112] S1202: Add 0.10 g of KCl-NH4Cl mixed salt to 4.90 g of sample A1 in a ratio of KCl:NH4Cl of 1:4, heat in a 60°C water bath with stirring for 30 min, and cool at 0°C to obtain a sample β4 phase change composite material.

[0113] The phase change temperature of the phase change composite material measured by differential scanning calorimetry (DSC) is 33.3℃, ​​and the phase change enthalpy is 164.6J / g.

[0114] Comparative Example 5

[0115] This comparative example provides a method for preparing a β5 phase change composite material, which specifically includes:

[0116] S1301: Add 2.14 g Na2SO4 and 0.15 g borax to 2.71 g BC (solid content 0.8 wt%) aqueous dispersion, stir well, heat and stir in a 60°C water bath for 30 min, and then cool at 0°C to obtain sample A1.

[0117] S1302: Add 0.15 g of KCl-NH4Cl mixed salt to 4.85 g of sample A1 in a ratio of KCl:NH4Cl of 1:4, heat and stir in a water bath at 60°C for 30 min, and cool at 0°C to obtain a sample β5 phase change composite material.

[0118] The phase change temperature of the phase change composite material measured by differential scanning calorimeter (DSC) is 32.2°C, and the phase change enthalpy is 145.7J / g; the thermal conductivity of the phase change material measured by hot disk is 0.75W / m·K.

[0119] Comparative Example 6

[0120] This comparative example provides a method for preparing a β6 phase change composite material, which specifically includes:

[0121] S1401: Add 2.14 g Na2SO4 and 0.15 g borax to 2.71 g BC (solid content 0.8 wt%) aqueous dispersion, stir well, heat and stir in a 60°C water bath for 30 min, and then cool at 0°C to obtain sample A1.

[0122] S1402: Add 0.20 g of KCl-NH4Cl mixed salt to 4.80 g of sample A1 in a ratio of KCl:NH4Cl of 1:4, heat and stir in a water bath at 60°C for 30 min, and cool at 0°C to obtain a sample β6 phase change composite material.

[0123] The phase change temperature of the phase change composite material measured by differential scanning calorimetry (DSC) is 31.0℃, and the phase change enthalpy is 124.4J / g.

[0124] Comparative Example 7

[0125] This comparative example provides a method for preparing a β7 phase change composite material, which specifically includes:

[0126] S1501: Add 2.14 g Na2SO4 and 0.15 g borax to 2.71 g BC (solid content 0.8 wt%) aqueous dispersion, stir well, heat and stir in a 60°C water bath for 30 min, and then cool at 0°C to obtain sample A1.

[0127] S1502: Add 0.25 g of KCl-NH4Cl mixed salt to 4.75 g of sample A1 in a ratio of KCl:NH4Cl of 1:4, heat and stir in a water bath at 60°C for 30 min, and cool at 0°C to obtain a sample β7 phase change composite material.

[0128] The phase change temperature of the phase change composite material was measured by differential scanning calorimetry (DSC) and was found to be 30.3°C, and the phase change enthalpy was 117.1 J / g. The thermal conductivity of the phase change material was measured by a hot disk and was found to be 0.81 W / m·K.

[0129] Comparative Example 8

[0130] This comparative example provides a method for preparing an A8 phase change composite material, which specifically includes:

[0131] S1601: Add 2.14 g Na2SO4 and 0.15 g borax to 2.71 g BC (solid content 0.8 wt%) aqueous dispersion, stir well, heat and stir in a 60°C water bath for 30 min, and then cool at 0°C to obtain sample A1.

[0132] S1602: Add 0.35 g of KCl-NH4Cl mixed salt to 4.65 g of sample A1 in a ratio of KCl:NH4Cl of 1:4, heat in a water bath at 60°C with stirring for 30 min, and cool at 0°C to obtain a sample β8 phase change composite material.

[0133] The phase change temperature of the phase change composite material measured by differential scanning calorimetry (DSC) is 27.0℃, and the phase change enthalpy is 81.9J / g.

[0134] Table 1 Performance test of embodiments and comparative examples

[0135] sequence name Phase transition temperature℃ Phase change enthalpy J / g Thermal conductivity W / m·K Example 1 5BN-KN1 34.2 170.2 1.42 Example 2 5BN-KN3 31.1 147.7 1.55 Example 3 5BN-KN5 28.3 118.9 1.49 Example 4 5BN-KN7 26.2 103.7 1.55 Example 5 3BN-KN3 31.8 160.4 1.33 Example 6 1BN-KN3 31.4 159.4 1.12 Comparative Example 1 β1 35.7 231.9 0.6 Comparative Example 2 β2 37.1 208.1 1.34 Comparative Example 3 β3 35.3 204.6 0.73 Comparative Example 4 β4 33.3 164.6 / Comparative Example 5 β5 32.2 145.7 0.75 Comparative Example 6 β6 31.0 124.4 / Comparative Example 7 β7 30.3 117.1 0.81 Comparative Example 8 β8 27.0 81.9 /

[0136] In order to verify the thermophysical properties of the temperature-adjustable thermally conductive phase change composite material prepared in the embodiment of the present application, the performance test of the temperature-adjustable thermally conductive phase change composite material prepared in the embodiment and the comparative example was carried out, and the results were as follows: Figures 1 to 6 As shown. Among them, Figure 1 The step cooling curves of the temperature-adjustable thermal conductive phase change composite materials 5BN-KN1, 5BN-KN3, 5BN-KN5 and 5BN-KN7 prepared in the examples of the present application; Figure 2 Phase separation diagram of the temperature-adjustable thermally conductive phase change composite materials 5BN-KN1, 5BN-KN3, 5BN-KN5 and 5BN-KN7 prepared in the examples of the present application; Figure 3 Phase change latent heat and phase change temperature diagram of the temperature-adjustable thermal conductive phase change composite materials 5BN-KN1, 5BN-KN3, 5BN-KN5 and 5BN-KN7 prepared in the examples of the present application;

[0137] Figure 4 The latent heat of phase change and the phase change temperature diagram of the temperature-adjustable thermal conductive phase change composite materials of 1BN-KN3, 3BN-KN3 and 5BN-KN3 prepared in the examples of the present application; Figure 5This is a cyclic stability diagram of the 5BN-KN3 temperature-adjustable thermally conductive phase change composite material prepared in an embodiment of the present application; Figure 6 This is a thermal conductivity diagram of the temperature-adjustable thermally conductive phase change composite materials 1BN-KN3, 3BN-KN3 and 5BN-KN3 prepared in the examples of the present application.

[0138] according to Figure 1 It can be seen that the step cooling curves of the temperature-adjustable thermally conductive phase change composite materials 5BN-KN1, 5BN-KN3, 5BN-KN5 and 5BN-KN7 prepared in the embodiments of the present application show that when 1, 3, and 5 wt% of the temperature regulator are added, the supercooling of the phase change material is very small, only 0.1°C, and when 7 wt% of the temperature regulator is added, the supercooling of the phase change material is 6.4°C, which leads to unstable physicochemical properties of the thermally conductive phase change composite materials.

[0139] according to Figure 2 It can be seen that the phase separation diagrams of the temperature-adjustable thermally conductive phase change composite materials 5BN-KN1, 5BN-KN3, 5BN-KN5 and 5BN-KN7 prepared in the embodiments of the present application show that there is only a small amount of liquid phase in the phase change material after melting, which substantially improves the phase separation phenomenon of the inorganic phase change material.

[0140] according to Figure 3 It can be seen that the phase change latent heat and phase change temperature diagram of the temperature-adjustable thermally conductive phase change composite materials 5BN-KN1, 5BN-KN3, 5BN-KN5 and 5BN-KN7 prepared in the embodiments of the present application show that the phase change temperature and phase change enthalpy of the thermally conductive composite phase change material with 5wt% BN content significantly decrease with the increase of the content of the added temperature regulator; when the content of the temperature regulator is 3wt%, the enthalpy value of the thermally conductive composite phase change material is 147.7J / g, and the phase change temperature is 31.1°C; when the amount of the temperature regulator added is 7wt%, the phase change temperature is reduced to 26.2°C, and the phase change enthalpy value is also reduced to 103.7J / g.

[0141] according to Figure 4 It can be seen that the phase change latent heat and phase change temperature diagram of the temperature-adjustable thermally conductive phase change composite materials 1BN-KN3, 3BN-KN3 and 5BN-KN3 prepared in the embodiments of the present application show that after adding 3wt% of the temperature regulator, the phase change enthalpy values ​​of the thermally conductive composite phase change materials with different BN contents are between 140-160J / g, and the phase change temperature is maintained at 30-32°C.

[0142] according to Figure 5It can be seen that the cyclic stability diagram of the 5BN-KN3 temperature-adjustable thermally conductive phase change composite material prepared in the embodiment of the present application keeps the phase change enthalpy loss rate of the 5BN-KN3 temperature-adjustable thermally conductive phase change composite material within 5% after 50 heating-cooling cycles, indicating that the prepared sample can maintain a good cycle service life in actual use.

[0143] according to Figure 6 It can be seen that from the thermal conductivity diagrams of the temperature-adjustable thermally conductive phase change composite materials of 1BN-KN3, 3BN-KN3 and 5BN-KN3 prepared in the embodiments of the present application, when the content of the fixed mixed salt is 3wt%, as the content of the thermally conductive filler BN increases, the thermal conductivity of the phase change material also increases accordingly; after adding 1, 3 and 5wt% BN, the thermal conductivities are 1.12W / m·K, 1.33W / m·K and 1.55W / m·K, respectively, which is 107% higher than that of the sample without BN, indicating that the addition of the thermally conductive filler effectively promotes heat transfer, enabling the material to respond to temperature changes more quickly.

[0144] The difference between the comparative example 1 of the present application and the embodiment 1 is that no thermal conductive filler and temperature regulator are added, so that it has a higher phase change temperature, a higher phase change enthalpy value, and a lower thermal conductivity; the difference between the comparative example 2 of the present application and the embodiment 1 is that no temperature regulator is added, so that it has a higher phase change temperature, a higher phase change enthalpy value, and a higher thermal conductivity; the difference between the comparative examples 3-8 of the present application and the embodiments 1-4 is that different proportions of temperature regulators are added and no thermal conductive filler is added, so that it has an adjustable phase change temperature, a higher phase change enthalpy value, and a lower thermal conductivity. Therefore, by strictly controlling the proportion of each component, the inorganic phase change material, the nucleating agent, the thickener, the thermal conductive filler and the temperature regulator are compounded, which is very critical for the prepared temperature-adjustable thermal conductive phase change composite material to have a phase change temperature close to room temperature and a high latent heat of phase change, no supercooling and excellent thermal conductivity.

[0145] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0146] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions recorded in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.

Claims

1. A method for preparing a temperature-adjustable thermally conductive phase change composite material, characterized in that: The preparation method comprises: 2.14 g of Na2SO4, 0.15 g of borax and 2.71 g of bacterial cellulose were heated and stirred, and then cooled to obtain a first composite; 4.75 g of the first composite and 0.25 g of boron nitride were heated and stirred, and then cooled to obtain a second composite; The second composite and the temperature regulator are heated and stirred, and then cooled to obtain a temperature-adjustable thermally conductive phase change composite material; Wherein, the temperature regulator is a mixed salt of KCl: NH4Cl in a ratio of 1:4; The ratio of the temperature regulator to the temperature-adjustable thermally conductive phase change composite material is 1 wt%, 3 wt%, and 5 wt%; The bacterial cellulose exists in the form of an aqueous dispersion, wherein the solid content is 0.8 wt %.

2. The method for preparing the temperature-adjustable thermally conductive phase change composite material according to claim 1, characterized in that: The heating and stirring is performed at a temperature of 40-80°C and a time of 0.2-2 h.

3. The method for preparing the temperature-adjustable thermally conductive phase change composite material according to claim 1, characterized in that: The cooling temperature is 0-10°C.

4. The temperature-adjustable thermally conductive phase-change composite material prepared according to the preparation method according to any one of claims 1 to 3 can be applied to battery outer packaging thermal management, wearable thermal management equipment and energy-saving buildings.

Citation Information

Patent Citations

  • Low-temperature inorganic phase-change energy storage material and preparation method thereof

    CN107201215A

  • Efficient composite phase change material and preparation method thereof

    CN108531136A

  • Phase change energy storage material and preparation method

    CN112940685A